FAKTOR INTERNAL YANG MEMPENGARUHI KELELAHAN KERJA PERAWAT DI PUSKESMAS WILAYAH KERJA KECAMATAN CICALENGKA DAN NAGREG KABUPATEN BANDUNG - Mulyani, Siti; Rejeki, Yunita Fitri (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2025)
Work fatigue is a source of problems for occupational health and safety in the workplace, both in the formal and informal sectors. Work fatigue is one of the crucial problems that needs to be addressed because it can result in several negative impacts such as lost work skills, decreased health conditions of workers which can trigger work accidents, decreased productivity and work performance. This type of research is quantitative research using descriptive methods. The population in this study were all 30 nurses. The sampling technique used was a total sampling of 30 people. Data analysis used Univariate and Bivariate Analysis. The results of the Bivariate Analysis showed the p value for the variable Nutritional Status (p = 0.014) and Sleep Quality, p = 0.000. The conclusion of this research is that there is an influence of Nutritional Status and Sleep Quality on work fatigue in nurses. To minimize the emergence of work fatigue experienced by nurses, Puskesmas management can provide a comfortable rest room by placing aromatherapy in the corner of the room, holding outbound activities to strengthen teamwork. Nurses must also maintain a good sleep pattern by paying attention to sleep duration, doing exercise, paying attention to and consuming nutritious and balanced food, maintaining body weight so that nutritional status remains normal so as not to experience work fatigue and helping each other in order to reduce workload.